Original articleEffects of hypothermia on ex vivo microglial production of pro- and anti-inflammatory cytokines and nitric oxide in hypoxic-ischemic brain-injured mice - Matsui, Tomohiro; Kida, Hiroyuki; Iha, Takuya; Obara, Tabito; Nomura, Sadahiro; Fujimiya, Tatsuya; Suzuki, Michiyasu (Folia Neuropathologica, 2014)
Introduction : Activated microglia produce neurotoxic factors, including pro-inflammatory cytokines and nitric oxide (NO), in response to neuronal destruction. Therapeutic suppression of microglial release of these factors by various approaches including hypothermia is considered to be neuroprotective after severe brain damage. We examined the effects of hypothermic culture on the production of pro- and anti-inflammatory cytokines and NO in ex vivo microglia that were derived from mice with hypoxic-ischemic (HI) brain injury, through the stimulation of toll-like receptors (TLRs) that play significant roles in the pathological processes underlying a sterile central nervous system injury. Material and methods : Two-day-old mice underwent the right common carotid artery ligation followed by 6% oxygen for 30 min, and thereafter were placed at 37°C for 24 h, after which microglia were isolated and then cultured with TLR2 and TLR4 agonists at 33°C and 37°C. Cytokine and NO levels in culture supernatants were measured. Results: Compared with 37°C, hypothermia (33°C) reduced the production of tumour necrosis factor-alpha (TNF-α: a pro-inflammatory cytokine) at 6 h and interleukin-10 (IL-10: an anti-inflammatory cytokine) and NO at 48 h. Conclusions : In TLR-activated microglia that were derived from mice with HI brain injury, hypothermia reduced the production of TNF-α, IL-10, and NO temporally, a clinically relevant finding suggesting that neuroprotection conferred by therapeutic hypothermia is related to attenuation of early-phase and late-phase inflammatory factors as well as that of late-phase anti-inflammatory factor(s) released from microglia.